Nurse Practitioner Activities in Ontario Family Health Teams: Comparing Three Different Data Sources. - Rayner, Jennifer; Donald, Faith; Martin-Misener, Ruth; Glazier, Rick; Kopp, Alex (Nursing Leadership (1910-622X), 2020)
Background: Despite the increase in nurse practitioners (NPs) working in primary healthcare, little standardized data are available to understand NP activities at the system level. The Nurse Practitioner Access Reporting system (NPAR), a pilot project underway at 40 family health teams in Ontario, involves NPs recording and submitting standardized codes. The codes are intended to reflect NPs' clinical activities, using an existing physician claim system. The study compared how well data collected through NPAR reflect NPs' activities. Methods: The mixed-methods approach was used involving NPAR data, focus groups and time and motion data. Results: All data sources indicated that NPs spent the majority of their time on direct patient care. Qualitative data and time and motion data revealed gaps in NPAR data, for example, codes that fail to capture activities unique to the NP role. Conclusion: Analysis of NPAR, time and motion and qualitative data provided a distinctive opportunity to examine NP-reported activities and patient characteristics; however, NPAR data did not adequately describe the scope or breadth of activities of NPs practising in primary healthcare.